Lechniccy – z dziejów publicznego zaangażowania ziemiaństwa w Drugiej Rzeczypospolitej - Waingertner, Przemysław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
In this article, based on studying archival materials and press, a history of Lechnickis brothers – Zdzisław, Tadeusz and Felicjan – in the Second Republic of Poland is showed. They were Polish landowners, politicians and social activists – leaders of the Polish Youth Union “Zet” and the Patriotic League. Before the First World War they supported a fight for the independence, including a military struggle. In the face of war Lechnickis decided to suport Józef Piłsudski and his military action. In the interwar Poland they tried to create a political movement, supporting Piłsudski’s activity and his coup d’etat. Lechnickis created an ideology for the Sanacja political camp which was formed then. Zdzisław, Tadeusz and Felicjan declared for democratic system and opposed dictatorship, however, they criticized parliamentary system, demanding presidential one. They supported a development of the municipal autonomy and tolerant policy towards national minorities, promoting state assimilation. As the leaders of “Zet” and the Patriotic League supported also the etatism and state interventionism in economy. The state was perceived by Lechnickis as the highest form of organization for political, economic, social and national life, as well as their political activity had reference to state interest.